Entre geografia e matemática: uma narrativa sobre o tratamento do conceito de área em livros didáticos - Soares, Marilene Caitano Reis Almeida (Universidade Federal de São Carlos, 2026)
Considering that the concept of area is present in both Geography and Mathematics education, it may be regarded as interdisciplinary within the context of Basic Education. The general objective of the research presented in this dissertation was to analyze the concept of area within the context of school Geography, taking as its object the way this concept is presented in Geography textbooks. Grounded in cultural-historical theory and narrative inquiry, the study understands experience as both phenomenon and method, recognizing that the researcher and the research mutually constitute one another through the movement of narrating, analyzing, and interpreting lived experience. The research question guiding the study was: how is the interdisciplinary concept of area presented in Geography textbooks, and what implications does this approach produce in the teacher-researcher’s reflections on her teaching and learning processes? Based on this objective and question, the analysis focused on two textbook collections and on the production of narratives of teaching experience. Methodologically, the research adopts a qualitative approach organized into four analytical categories: (1) the approach to the concept of area in textbooks; (2) reading space, graphic representations, and the confusion between area and territory in textbooks; (3) proposed activities and the mediation of knowledge; and (4) in interdisciplinarity with Mathematics, the concept of area becomes a movement of thought which, at the stage of synthesis, comes to compose an interpretative unity guided by historical-dialectical logic. The results show that, although recurrent, the concept of area appears in textbooks in a fragmented way, marked by silences and reductions that compromise its logical-historical meaning, often being treated as a technical procedure devoid of conceptual mediation. The narratives of the teacher-researcher reveal that this limiting form of approach directly interferes with pedagogical practice, requiring teaching interventions so that the concept acquires meaning and becomes constituted as an instrument of thought. Furthermore, it becomes evident that interdisciplinarity between Geography and Mathematics is not realized in textbooks as an effective articulation, but rather as a juxtaposition, which limits the understanding of area in its relationship with lived space. The central thesis defended is that the interdisciplinary articulation between Geography and Mathematics, guided by historical-dialectical logic, enhances the teaching of the concept of area by overcoming its technical reductionism, enabling narratives of experience to be translated into analytical elements supported by a consistent theoretical and methodological structure. It is concluded that teaching the concept of area implies fostering theoretical thinking capable of understanding space in its materiality, historicity, and social meaning, integrating calculation, territory, and experience.
Between geography and mathematics: a narrative on the treatment of the concept of area in textbooks
Keywords: Pesquisa Narrativa;; Teoria Histórico-Cultural;; Conceito de Área;; Livro Didático de Geografia;; Prática Pedagógica; Narrative Inquiry;; Cultural-Historical Theory;; Concept of Area;; Geography Textbook;; Pedagogical Practice.; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade